THESIS TITLE: STRATEGIES FOR ANALYZING IELTS SPEAKING PART 2 RESPONSES - Shamsuddinova Ruqiyaxon; Abduraxmonov Toʻraxon (TADQIQOTLAR, 2025)
Introduction: IELTS Speaking Part 2, also known as the “long turn,” requires the test-taker to speak for 1–2 minutes on a given topic. Analyzing responses in this section involves understanding how well the candidate addresses both the main question and its sub-points. Effective analysis strategies help improve coherence, fluency, and vocabulary.